ANALISIS PENYELESAIAN SOAL BANGUN RUANG SISI DATAR DINILAI DARI KEMAMPUAN PEMECAHAN MASALAH MATEMATIK SISWA SMP - Ninda Naila Sartika Indah Permana; Adi Nurjaman (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
Problem solving is one of the skills that is quite important for every student to have, because it is closely related to everyday life. To solve a mathematical problem, students are expected to be able to identify the adequacy of data, make mathematical forms, determine and implement strategies, present results, and apply mathematics in a meaningful way. Analysis of the difficulty of solving mathematical problems on the material of blocks, cubes, pyramids, and prisms is the goal of the research conducted and qualitative descriptive is the method in this study. The eighth grade students of SMP Negeri in Cimahi are the subjects to be studied and totaling 34 students. The results of the data analysis are in poor qualifications regarding the problem-solving abilities of students. This is because students are not used to working on non-routine questions.